2015
DOI: 10.1039/c5ra10895k
|View full text |Cite
|
Sign up to set email alerts
|

Highly transparent poly(2-ethyl-2-oxazoline)-TiO2nanocomposite coatings for the conservation of matte painted artworks

Abstract: A nanocomposite coating based on TiO2 nanoparticles and poly(2-ethyl-2-oxazoline) is used as consolidant of matte paintings (such as temperas), by exploiting bulk scattering phenomenon to mimic the surface diffusive properties of the painted surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 43 publications
3
18
0
Order By: Relevance
“…Paint layers prepared with Aquazol 500 without pigments did not show significant modifications during artificial ageing, in agreement with the data reported in the literature [23]. This thus confirms its potential for use as a binder for retouching paints in the restoration of works of art.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Paint layers prepared with Aquazol 500 without pigments did not show significant modifications during artificial ageing, in agreement with the data reported in the literature [23]. This thus confirms its potential for use as a binder for retouching paints in the restoration of works of art.…”
Section: Discussionsupporting
confidence: 91%
“…Aquazol 500 is now being used to retouch paintings. This study highlights that the stability of the polymer, as shown in a previous study limited to TiO2 nanoparticles [23], is affected by the presence of pigments. This is particularly the case of organic lakes containing an inorganic fraction in the formulation, leading to different physico-chemical phenomena, depending on the nature of the pigment.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Furthermore, due to its low cytotoxicity and “living polymerization” characteristic, PEOX has been applied in electronic devices [ 14 , 15 ] biomedical applications including drug delivery [ 16 ], anti-fouling coatings individually or as a monomer of block copolymers [ 17 , 18 , 19 ]. PEOX can also be adopted as a coating material because of its good light stability and re-solubility [ 20 , 21 ]. However, up to now, the environment-friendly material PEOX has seldom been reported and evaluated as a consolidant for wall paintings.…”
Section: Introductionmentioning
confidence: 99%